(untitled) (International Journal of Engineering and Computer Science, 2017)
The Internet of Things (IoT) integrates a large number of physical objects that are uniquely identified, ubiqui- tously interconnected and accessible through the Internet. IoT aims to transform any object in the real-world into a computing device that has sensing, communication and control capabili- ties. There is a growing number of IoT devices and applications and this leads to an increase in the number and complexity of malicious attacks. It is important to protect IoT systems against malicious attacks, especially to prevent attackers from obtaining control over the devices. A large number of security research solutions for IoT have been proposed in the last years, but most of them are not standardized or interoperable. In this paper, we investigate the security capabilities of existing protocols and networking stacks for IoT. We focus on solutions specified by well-known standardization bodies such as IEEE and IETF, and industry alliances, such as NFC Forum, ZigBee Alliance, Thread Group and LoRa Allianc.